Density-dependent numerical simulations of the impact of underground dams on groundwater storage on Samui island, Thailand. Issue 2 (3rd July 2017) - Arlai, Phatcharasak; Koch, Manfred
Abstract : Samui island in southern Thailand has become an increasingly attractive tourist spot over the last decades. However, the enormous numbers of tourists has led to deficits of the available water resources, mainly surface water stored in a few reservoirs across the island during the dry season of the year, which is also the main tourist season. The Department of Groundwater Resources (DGR) has been aware of this problem and initialized a project of underground dam construction which is supposed to impede the natural groundwater outflow toward the sea and, hence, to increase the usable groundwater storage on Samui island during the dry season. The dam will be initially designed as two impermeable underground-walls amid the two rock-gorges that cut through the three layers of the aquifer system, reaching down to a maximum depth of about 50 m. A top of the 2 m wide dam which ends below the upper unconfined aquifer layer, a vertical layer of high permeability will be specified, so that a "spillway-like" over-flow of the groundwater with only minor impacts on the subsurface ecology downstream toward the sea will be generated. Based on this conceptual model, a 3D-variable density groundwater flow and transport model has been set up and calibrated in both steady and transient modes. In the subsequent modeling analysis the underground dam with the above spillway characteristics has been embedded into the model by specifying the corresponding vertical curtains of low and high conductivity, respectively. Finally, groundwater pumps upstream of the underground dams have been included into the model. Simulations without and with the hydraulic structures have been performed to ascertain the differences with respect to groundwater levels and storage and to evaluate the overall functionality of the underground dam. The results show that the underground dam is able to raise groundwater levels, that is, groundwater storage. The budget analysis of the simulation sets indicates that the underground dams serve well their purpose, particularly, for long dry spells, as more groundwater can be pumped out than would be possible without such a hydraulic structure. Finally, analyses of the seawater intrusion problem based on (1) the Ghyben-Herzberg formula, (2) analytical solutions of the sharp interface problem under Dupuit's assumption, and (3) using the density-dependent SEAWAT – flow and solute transport modeling of the transition zone have been carried out. Differences in the landward extensions of the seawater intrusion fronts for the analytical and numerical solutions are found; however, the general predictions of the analytical theory are supported by the SEAWAT model in general, that is, a landward progression of the seawater intrusion front for pumping conditions and a partly retreat again in the presence of the two underground dams. In any case, seawater intrusion in the coastal zone of the study region does not extend deep enough inland to adversely impact the quality of the pumped groundwater there.